Cultural Guidelines for Commercial Production of Interiorscape Anthurium - Jianjun Chen; Dennis B. McConnell; Richard J. Henny; Kelly C. Everitt (EDIS, 2003)
The intent of this article is to describe common species and cultivars in the foliage plant industry, provide guidelines for their culture and interior use, and list physiological problems that may be encountered during production and interiorscape use. This document is ENH956, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 1, 2003.